Exploring senior high school students’ mathematical critical thinking barriers and self-generated solutions: A hermeneutic phenomenological study - Susi Sulasti; Naif Mastoor Alsulami; Muhamad Galang Isnawan; Farah Heniati Santosa; Ronaldo Rafael Olivero-Acuña; Denilsón Andrés Silgado-Tuñón (Panicgogy International Journal, 2026)
Critical thinking is a foundational competency for mathematical problem-solving, yet Indonesian students continue to perform below international benchmarks such as PISA and TIMSS. Although prior studies have examined factors associated with weak mathematical critical thinking, few have explored the phenomenon directly through students’ own lived experiences using a hermeneutic phenomenological design, and fewer still have paired thematic analysis with generative artificial-intelligence assistance such as ChatGPT to support systematic coding. This study aimed to identify the factors underlying students’ low critical thinking skills in mathematics learning and to uncover the solutions students themselves proposed to overcome these barriers. A qualitative hermeneutic phenomenological approach was employed, using ChatGPT-assisted thematic analysis across six analytic tables covering factor codes, solution codes, categories, and themes. Participants were ten Grade XII students (nine female, one male; aged 16–17 years) at a public senior high school in West Lombok Regency, Indonesia, selected through purposive sampling because they had been identified as experiencing persistent difficulty with mathematical critical thinking. Data were collected through an open-ended questionnaire and analyzed following six phases of thematic analysis. The findings revealed four major factor themes: difficulty memorizing and understanding formulas, weak habits of critical thinking and information-seeking, suboptimal use of technology, and low internal motivation. Correspondingly, students proposed four solution themes centered on active learning strategies, contextual and reflective learning, educational use of technology, and cultivation of internal motivation. These findings suggest that mathematics teachers should adopt active, contextual, and technology-integrated pedagogies, supported by ongoing professional development, so that critical thinking is nurtured as a core learning outcome rather than a byproduct of content mastery.